The relationship between social media use and pregnancy-related body image - Diane L Rosenbaum; Meghan M Gillen; David J Hutson (Women's Health)
Background: Social media negatively affects body image, but few have investigated its impact on pregnancy-related body image. Pregnancy represents a vulnerable period for body image, and poor body image has negative implications for health. Objectives: We aimed to (1) understand relations of social media and pregnancy-related body image variables, (2) examine differences in social media use and body image based on demographic characteristics, and (3) evaluate whether type of social media use (i.e., active versus passive) was differentially related with body image based on time spent on social media. Design: This was a cross-sectional study. Methods: We recruited an online sample of women ( N  = 154) experiencing early motherhood, as defined by giving birth within the past 5 years. We examined social media use (e.g., amount of time, type of use) on Facebook, Instagram, and Twitter in relation to pregnancy-related body image questionnaires. Results: Passive use (e.g., viewing others’ content rather than creating original content) and greater time on Facebook were independently related to lower positive body image. Those who passively used Facebook for the longest amount of time had the lowest positive body image. No significant effects were found for Instagram or Twitter. Conclusion: Spending more time passively viewing others’ content may facilitate social comparison, reducing positive feelings about one’s own body. Social media may constitute a source of pressure and scrutiny for women, resulting in lowered pregnancy-related body image.